Molluscum contagiosum eruption during therapy with methotrexate and abatacept: a clinical and dermoscopic case study (Dermatology Reports, 2022)
The use of multiple drugs acting as modulators of the immune system are common among patients with severe autoimmune diseases. In these clinical scenarios, great attention should be placed on diagnosing infective cutaneous disorders that can underly iatrogenic immunosuppression. Here within, we report a rare case of molluscum contagiosum eruption on the face and the scalp during an immunomodulating treatment for rheumatoid arthritis, with clinical and dermatoscopic characterization.